Nasi Minyak, A Product Of Arabian Culinary Heritage, As A Gastronomy Tourism In Palembang City - Febriyanti, Yuyun (Gastronomy Tourism Journal, 2020)
Gastronomy tourism is a food tasting activity that does not only focuses on food but also emphasizes cultural aspects as well as studies the history of the food itself. Indonesian gastronomy is believed to be formed from a fusion of culture and food between natives, such as Chinese, Indians, Middle East, Europe, Portuguese and Dutch. Palembang is a city that is rich in culture from customs to cuisine. Palembang is influenced by various cultures such as Chinese, Middle East, and Arabic. One of Palembang's culinary that is influenced by Arabic culture is nasi minyak (Indonesian fragrant spiced rice). The method used in this research is descriptive qualitative. While the data processing technique is done by observation and interview techniques. The results show that nasi minyak is similar to the original Arabian kabsa rice, introduced by Arab descendants namely Al-Munawar community, when they threw a party. However, they served the cuisine by adapting the taste to the Palembang people’s. The ingredients used to make rice oil are white rice, ginger oil, onions, garlic, coriander, cumin, cinnamon, star anise, cloves, cardamom, lemongrass, broth, nutmeg, sweet fennel, ginger, bay leaf, milk, tomato/tomato sauce, and turmeric.